Soil Properties as Affected by Soil Conservation Practices and Soil Depths in Uwite Watershed, Hadero Tunto District, Southern Ethiopia - Mulugeta Hadaro; Tuma Ayele; Sharma Parshotam Datt; Rahel Teshome (Applied and Environmental Soil Science)
Soil is a precious natural resource, forming the basis for sustained ecosystem services for the mankind. Its degradation due to the ever-increasing anthropogenic influence is, however, threatening food security and quality of the environment in many regions. The present investigation was, therefore, undertaken with an objective of assessing the effect of soil and water conservation practices of soil bund and Fanya juu terrace compared to no conservation practice on cultivated soils of Uwite watershed in Hadero Tunto District, southern Ethiopia. Soil sampling sites were selected both from the farm fields, where soil conservation structures were raised for the last 10 years, and from fields where there was no conservation practice. A total of eighteen composite soil samples (3 conservation practices × 2 depths, 0–15 and 15–30 cm, ×3 replicates) were collected and analyzed for different physical and chemical soil parameters. The results were subjected to analysis of variance using the General Linear Model of two-way ANOVA by RCBD with factorial arrangement using SAS software. Both practices, statistically similar to each other, indicated significant improvement in soil parameters compared to no conservation practice in higher content of clay, lower bulk density, higher total porosity, higher moisture content, higher pH, higher soil organic matter, higher percent base saturation, higher cation exchange capacity, and higher amounts of macro- (N, P, K, Ca, Mg, and S) and micronutrients (Fe, Zn, and Cu). The surface soil layer (0–15 cm) was significantly superior to the subsurface layer (15–30 cm) in most of these soil parameters. Both practices of soil bund and Fanya juu terrace merit their continuation on the existing lands and upscaling to other degraded areas for sustained land productivity and socioeconomic-environmental stability in the region